Mapping knowledge domain of acupuncture for Parkinson’s disease: a bibliometric and visual analysis - Zhao, Yanqing; Huang, Li; Li, Wentao (Frontiers in Aging Neuroscience, 2024)
Objective This study points to probing the inclination and mapping knowledge domain of acupuncture for Parkinson’s disease through bibliometrics. Methods A search was conducted on 1 February 2024 using the Web of Science to identify papers published on acupuncture for Parkinson’s disease. The analysis included scientific research, countries, organizations, authors/cited authors, keywords, journals, and cited references. Bibliometric data were analyzed using VOSviewer software, CiteSpace, GraphPad Prism, and Scimago Graphica. The studies on acupuncture for Parkinson’s disease were visualized as a network map according to the publication year. Results The cumulative publication trend on acupuncture for Parkinson’s disease is increasing year by year. China is the leading contributor in this field. International collaboration is predominantly concentrated in Europe, while institutional collaboration is chiefly limited to Chinese universities specializing in traditional Chinese medicine. Park HJ is the most prolific author, with “Movement Disorders” being the journal with the most publications. “Brain Research” is identified as a key journal, reflecting a focus on neuroscience. Kim SN is the most cited author, while Eisenberg DM is a prominent author in this field. Research topics such as mouse models, systematic reviews, and non-motor symptoms are frequently explored, with messenger RNA of substantia nigra emerging as a notable keyword in this field. Choi YG’s 2009 paper, published in the Neuroscience Letters journal, is a critical reference in this field. Key papers include Eisenberg DM’s 1998 study on randomized trials of acupuncture for non-motor symptoms of PD, as well as research focusing on the neuroinflammatory regulatory mechanisms of acupuncture for PD. Conclusion The bibliometric analysis offers an exhaustive generality of the advancement and worldwide trends in acupuncture treatments for Parkinson’s disease, shedding light on potential avenues for prospective research.